Biological and clinical implications of cancer stem cells in primary brain tumors - Maugeri-Saccà, Marcello; di Martino, Simona; De Maria, Ruggero (Frontiers in Oncology, 2013)
Despite therapeutic advances, glioblastoma multiforme (GBM) remains a lethal disease. The infiltrative nature of this disease and the presence of a cellular population resistant to current medical treatments account for the poor prognosis of these patients. Growing evidence indicates the existence of a fraction of cancer cells sharing the functional properties of adult stem cells, including self-renewal and a greater ability to escape chemo-radiotherapy-induced death stimuli. Therefore, these cells are commonly defined as cancer stem cells (GBM-SCs). The initial GBM-SC concept has been challenged, and refined according to the emerging molecular taxonomy of GBM. This allowed to postulate the existence of multiple CSC types, each one driving a given molecular entity. Furthermore, it is becoming increasingly clear that GBM-SCs thrive through a dynamic and bidirectional interaction with the surrounding microenvironment. In this article, we discuss recent advances in GBM-SC biology, mechanisms through which these cells adapt to hostile conditions, pharmacological strategies for selectively killing GBM-SCs, and how novel CSC-associated endpoints have been investigated in the clinical setting.